Kepemimpinan Multistaf Menurut Keluaran 18:13-27 Dan Implikasinya Bagi Pemimpin Gereja Masa Kini - Wulan Agung (Sekolah Tinggi Teologi Nusantara, 2020)
Leadership is an important aspect of the organization. If leadership is less effective it will have an impact on organizational development. Therefore we need to think about the concept of leadership. The Bible shows that there is a concept of leadership that works effectively. To discuss this concept, the authors conducted an analysis of Exodus 18: 13-27, the writer looked at it as a biblical concept for multistaff leadership. From the results of the literature analysis of Exodus 18: 13-27, it is found that the concept of multistaff leadership represents leadership centered between the main leaders and the leaders below them to overcome the issues that arise. In a multistaff leadership system the recruitment of prospective leaders who have the qualifications desired by God, then gives approval and division of responsibilities. This leadership model is still very relevant for church leaders today.Kepemimpinan merupakan aspek penting dalam sebuah organisasi. Jika kepemimpinan kurang efektif akan berdampak para perkembangan organisasi. Oleh sebab itu perlu sebuah gagasan konsep kepemimpinan. Alkitab menunjukkan bahwa ada konsep kepemimpinan yang berjalan efektif. Untuk meneliti konsep tersebut, penulis melakukan analisis terhadap Keluaran 18:13-27 penulis pandang sebagai konsep alkitabiah untuk kepemimpinan multistaf. Dari hasil analisis literatur terhadap Keluaran 18:13-27 ditemukan konsep bahwa kepemimpinan multistaf merupakan kepemimpinan yang berpusat pada kerjasama antara pemimpin utama dan pemimpin yang ada dibawahnya untuk mengatasi perkara-perkara yang muncul. Dalam system kepemimpinan multistaf perekrutan calon pemimpin yang memiliki kualifikasi yang dikehendaki Allah, kemudian memberikan pengajaran dan pembagian tanggung jawab. Model kepemimpinan tersebut masih sangat relevan bagi pemimpin gereja masa kini.